The Judge's Paradigm In Deciding Criminal Cases Of Sexual Violence From A Victimological Perspective - Muh Sutri Mansyah; Hadi Supriyanto; Kaswandi; Erick Bason; Sulayman (Buana Gender: Jurnal Studi Gender dan Anak, 2024)
Criminal acts of sexual violence are widespread in society, and the aim of the research is to study and analyze a decision. The research methods used by researchers are normative juridical with case, statutory, and philosophical approaches. The primary legal material is the Sexual Violence Crime Law and Decision Number 72/Pid.Sus/2023/PN.Bau. while secondary materials: books, journals, etc., the interpretation used is grammatical and systematic interpretation. The results of the research show that the paradigm used by the Panel of Judges does not have a victimology perspective, as evidenced by the statement expressed by the victim witness who explained that the defendant was not the perpetrator of a crime of sexual violence, while the actual perpetrator had been appointed by the victim witness based on the photo submitted by the Counselor. The law and the perpetrator are still at large, while the defendant was legally and convincingly found guilty of committing the crime of sexual immorality. Therefore, the Panel of Judges ignored the facts of the trial. Apart from that, the panel of judges did not interpret the victim's witness statement as a standalone piece of evidence as regulated in the Sexual Violence Crime Law. So the author's suggestion is that it is important for the judge to have the victim's perspective, in this case, what the victim said is information that must be acknowledged at trial and It is necessary to evaluate the panel that examined and decided the case.